Examining the Uniformity Model of Received Premium Rates on Innovation in the Financial Management Policies of the Social Security Organization - Mohammadlu, Ahmadreza; Asgari, Farid; Nazari, Abdollah; Khalili, Farzaneh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of the present research is to examine the impact of uniform premium rate models on innovation in policies, reserves, and financial behaviors of the Social Security Organization. Methodology: The research methodology adopted was mixed qualitative-quantitative. In the qualitative section, the sample consisted of experts familiar with the subject, and through snowball sampling, 20 individuals were determined as the sample size. The population of the current study consists of managers and employees of the General Administration of Tehran Province’s districts. The sample size was determined to be 267 individuals, based on Cochran’s table and random sampling method. The data collection method in the qualitative part was library and field research, and in the quantitative part, it was field research, which was conducted using a researcher-made questionnaire. The validity of the questionnaire was verified through expert opinions, and Cronbach’s alpha method was utilized to assess reliability. For data analysis, grounded theory method was used in the qualitative section, and structural equation modeling and PLS4 software were used in the quantitative section. Findings: The findings indicated that 37 sub-components were identified for the model, which includes 7 causal factors, 8 contextual factors, 7 intervening factors, 11 strategies, and 4 outcomes. Furthermore, the model fitting results indicate the appropriateness of the proposed model. Conclusion: This study successfully identified key components and their impacts on the Social Security Organization’s financial management policies through a comprehensive mixed-method approach. Notably, strategies significantly influence outcomes, underlining the importance of effective strategic planning and intervention in enhancing organizational performance and achieving desired financial stability and innovation.